Pengaruh Model Pembelajaran Generatif Terhadap Kemampuan Berpikir Kritis Fisika Ditinjau Dari Pengetahuan Awal Peserta Didik - Hevida Aulia Yatmi; Wahyudi Wahyudi; Syahrial Ayub (Department of Physics Education, Universitas Mataram, 2019)
This research aims to determine: (1) the effect of generative learning models on students' critical thinking abilities in physics; (2) the effect of initial knowledge on students' critical thinking abilities in physics; (3) the interaction between generative learning models with initial knowledge of students' critical thinking physics abilities. This type of research is a quasi-experimental 2x2 factorial design. The population were all students of class X MIA SMAN 1 Gunungsari in the 2018/2019 school year. The research sample was taken by using purposive sampling technique, so students in class X MIA 3 were selected as the experimental class and students in class X MIA 4 were as the control class. Initial knowledge data were taken using multiple choice tests of 10 questions and critical thinking abilities data using 5 question essay tests. The results of the data were analyzed using two-way analysis of variance with a significance level of 5%. The results showed that: (1) there was an influence of generative learning models on students' critical thinking abilities in physics; (2) there is an influence of initial instruction on students' critical thinking abilities in physics; (3) there is no interaction effect between the generative learning model and initial knowledge on the students' critical thinking abilities in physics.